2019
DOI: 10.1007/jhep12(2019)101
|View full text |Cite
|
Sign up to set email alerts
|

Hanany-Witten transition in quantum curves

Abstract: It was known that the U(N ) 4 super Chern-Simons matrix model describing the worldvolume theory of D3-branes with two NS5-branes and two (1, k)5-branes in IIB brane configuration (dual to M2-branes after taking the T-duality and the M-theory lift) corresponds to the D 5 quantum curve. For deformations of these two objects, on one hand the super Chern-Simons matrix model has three degrees of freedom (of relative rank deformations interpreted as fractional branes in brane configurations), while on the other hand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(65 citation statements)
references
References 110 publications
(309 reference statements)
5
60
0
Order By: Relevance
“…The matrix models associated with these gauge theories also can be written as the partition functions of ideal Fermi gases when all the nodes have equal ranks, and much studied in the Fermi gas description [3,[27][28][29][30][31][32] as with the ABJ(M) theory. However, when the ranks are different, so far the Fermi gas formalism is applied only to special cases such as theories with gauge groups consisting of four unitary groups [33,34].…”
Section: Jhep10(2020)158mentioning
confidence: 99%
See 4 more Smart Citations
“…The matrix models associated with these gauge theories also can be written as the partition functions of ideal Fermi gases when all the nodes have equal ranks, and much studied in the Fermi gas description [3,[27][28][29][30][31][32] as with the ABJ(M) theory. However, when the ranks are different, so far the Fermi gas formalism is applied only to special cases such as theories with gauge groups consisting of four unitary groups [33,34].…”
Section: Jhep10(2020)158mentioning
confidence: 99%
“…It was revealed that some types of quantum curves obey the Weyl group symmetry of SO (10) and the exceptional groups [35,36]. Furthermore, it was found in [34] by connecting the SO (10) quantum curve to the rank deformed theories with four nodes without using the Fermi gas formalism that the Hanany-Witten transition is realized as a portion of the Weyl group symmetry of SO (10). This fact implies that quantum curves play an important role in understanding M2-brane physics.…”
Section: Jhep10(2020)158mentioning
confidence: 99%
See 3 more Smart Citations